Mobile Usage at the Base of the Pyramid : Research Findings from Kenya and South Africa - World Bank (Washington, DC, 2014)
While the growth of mobile communications in developing countries has been phenomenal, using mobile phones and applications to meet human and economic development goals is not widespread, for they have not proven acceptable or desirable to the locality into which they are introduced. Therefore, it is deduced that technical know-how and entrepreneurial acumen must be complemented by sociocultural understanding. InfoDev's Mobile Use at the Base of the Pyramid program seeks to contribute to this agenda through on-the-ground studies in developing markets. The first phase of this program supported both qualitative and quantitative research on mobile usage by low-income populations in Kenya and South Africa. This report documents the findings of this program.